The Impact of Technological Innovation on Small Business Growth in the Digital Economy - Saputra Roviano (Mustard Journal De Ecobusin, 2024)
Small firms play a central role in economic growth especially in the fast-growing digital economy. However, these ventures face limitations due to lack of resource bases, access to restricted markets and less developed technological strengths. This paper explores the impact of the technological innovation on the growth of small businesses, paying specific attention to the opportunities that digital tools provide to increase the efficiency of operations, reach a broader market, and become more competitive. The study incorporates a systematic literature review, policy documents, statistical data, and case studies through the qualitative descriptive methodology to show the use of technology in diverse contexts of small businesses in a practical way. The evidence suggests that technological innovation is one of the most important factors that drive the sustainability of an enterprise because it enhances productivity, customer interaction and optimization of the allocation of resources. Although these benefits exist, there are still challenges such as insufficient infrastructure, digital illiteracy and regulatory issues that hinder the best utilization of innovative solutions. It is therefore concluded that large-scale policy interventions- including government assistance, development of infrastructures, and capacity-building programs-are essential in order to help small businesses to take full advantage of technological changes. The lessons learned herein are of great support to policy makers, business leaders, and researchers and reinforces the importance of small businesses as drivers of inclusive development, as well as, resiliency in the digital era.